Modelling future trends in cystic fibrosis demography using the French Cystic Fibrosis Registry: update and sensitivity analysis. Issue 2 (3rd August 2017) - Burgel, Pierre-Régis; Bellis, Gil; Elborn, J. Stuart
Working with a group of investigators from the European Respiratory Society (ERS)/European Cystic Fibrosis Society (ECFS) task force for the "Provision of care in adults with cystic fibrosis (CF)" [1], we have previously modelled future trends in CF demography in European countries by calculating flows of patients entering and exiting CF cohorts in each country [2]. In that report, we used individual country data contained in the ECFS Patient Registry and were able to calculate demographic forecasts for several European Countries, including France [2]. These forecasts, which were based on the assumption that major demographic trends remained stable over time, suggested that a major increase in the number of CF adults was expected in western European countries by 2025 [1, 2]. In France, our forecast predicted an increase by 45.5% in the CF population between 2010 and 2025, corresponding to an increase by 18.4% in the paediatric population and an increase by 75.7% in the adult population [2]. Data confirm that a major increase in the adult cystic fibrosis population is expected within 10 years in France http://ow.ly/8LhD30cKvO7